Living with elephants: A case study from Kavango‐Zambezi Transfrontier Conservation Area in Zimbabwe - Muhammad Faizan Usman; Martin Reinhardt Nielsen; Sébastien Le Bel; Maxwell Phiri; Patrice Grimaud (People and Nature, 2025)
Abstract The Kavango‐Zambezi Transfrontier Conservation Area (KaZa TFCA) is home to one of the largest populations of African savanna elephants (approximately 227,000), a species iconic for ecological balance but also a major driver of human–elephant conflict (HEC). This study investigates how spatial and socio‐economic factors shape household perceptions and tolerance towards elephants in the Zimbabwean part of KaZa TFCA. Using a survey sample of 668 households experiencing HEC, we analysed the impact of proximity to forests, protected areas and water points on conflict intensity and community responses. Our findings reveal that households closer to these conflict‐prone features experience higher exposure to elephants, resulting in significant tangible costs, such as crop loss and property damage, and increased emotional stress. Among these features, proximity to forests emerged as the strongest predictor of HEC, followed by protected areas, with water points having a lesser influence. Distance to these features was found to mediate tolerance through its effects on tangible costs, intangible benefits and mitigation efforts. Intangible benefits, including an appreciation of elephants' ecological roles and aesthetic value, emerged as the strongest determinants of tolerance, highlighting the importance of nurturing positive perceptions. However, the absence of tangible benefits, such as tourism revenue or financial incentives, coupled with the tangible costs of living alongside elephants, such as crop damage, significantly undermine household tolerance. The study stresses the need for spatially informed mitigation strategies, including participatory spatial planning, early‐warning systems and livelihood diversification through community‐based conservation initiatives. Establishing community conservancies in high‐conflict wards could provide tangible benefits while empowering communities to engage in wildlife management. These findings highlight the importance of integrating conservation objectives with the socio‐economic realities of local communities, offering pathways for coexistence in biodiversity hotspots like KaZa TFCA. Read the free Plain Language Summary for this article on the Journal blog.